Effectiveness of a community health worker-delivered care intervention for hypertension control in Uganda: study protocol for a stepped wedge, cluster randomized control trial - Rebecca Ingenhoff; Juliet Nandawula; Trishul Siddharthan; Isaac Ssekitoleko; Richard Munana; Benjamin E. Bodnar; Ivan Weswa; Bruce J. Kirenga; Gerald Mutungi; Markus van der Giet; Robert Kalyesubula; Felix Knauf (Trials, 2022)
Abstract Background Over 80% of the morbidity and mortality related to non-communicable diseases (NCDs) occurs in low-income and middle-income countries (LMICs). Community health workers (CHWs) may improve disease control and medication adherence among patients with NCDs in LMICs, particularly in sub-Saharan African settings. In Uganda, and the majority of LMICs, management of uncontrolled hypertension remains limited in constrained health systems. Intervening at the primary care level, using CHWs to improve medical treatment outcomes has not been well studied. We aim to determine the effectiveness of a CHW-led intervention in blood pressure control among confirmed hypertensive patients and patient-related factors associated with uncontrolled hypertension. Methods We will conduct a stepped-wedge cluster randomized controlled trial study of 869 adult patients with hypertension attending two NCD clinics to test the effectiveness, acceptability, and fidelity of a CHW-led intervention. The multi-component intervention will be centered on monthly household visits by trained CHWs for a period of 1 year, consisting of the following: (1) blood pressure and sugar monitoring, (2) BMI monitoring, (3) cardiovascular disease risk assessment, (4) using checklists to guide monitoring and referral to clinics, and (5) healthy lifestyle counseling and education. During home visits, CHWs will remind patients of follow-up visits. We will measure blood pressure at baseline and 3-monthly for the entire cohort. We will conduct individual-level mixed effects analyses of study data, adjusting for time and clustering by patient and community. Conclusion The results of this study will inform community delivered HTN management across a range of LMIC settings. Trial registration ClinicalTrials.gov NCT05068505 . Registered on October 6, 2021.